Revitalizing Local Economy Through Village Tourism: Case Study of Dusun Gojang Utara, Selayar Islands, South Sulawesi, Indonesia - Adhikerana, Asep Sunjaya; Nasruddin, Nasruddin; Zulkarnaen, Sultandar; Simandjuntak, Herman S.; Sugardjito, Jito; Rismayani, Andi (Journal of Business on Hospitality and Tourism, 2021)
The study was done in March 2020 in Dusun Gojang Utara, Bontomarannu Village, Bontomanai Sub-district, Selayar Islands District, South Sulawesi, Indonesia, aiming at exploring the opportunity and feasibility of “Kenari Forest” as a tourist attraction. A descriptive-status approach was used in this study that was sought to answer questions about real-life situations, and in addition, the scoring of potential tourism object/attraction utilized the 2003 ADO-ODTWA Guideline. Overall, Dusun Gojang Utara has a high potency as a community-based tourism destination, although there are four criteria needed improvement, nanely: accessibility, surrounding conditions, management and services, and climate. Unfortunately, Dusun Gojang Utara as a tourist village is yet to be the priority of the local government,. Indeed, as part of the Bontomarannu Village, this dusun is included as an agro-tourism development area, but the potential of this dusun is not for agro-tourism, instead its tourism attraction resides in the local livelihood itself.